2016
DOI: 10.1080/1331677x.2016.1175726
|View full text |Cite
|
Sign up to set email alerts
|

Corporate capital structure: the case of large Croatian companies

Abstract: , split, Republic of croatia; b Faculty of tourism and organizational sciences, insurance supervisory agency of Republic of macedonia, skopje, University st. kliment ohridski, ohrid, Republic of macedonia ABSTRACT A growing body of research literature deals with the debt policy decisions of companies. Although the subject of corporate capital structure has been intriguing scientists for a number of years, very little research has been conducted on the sample of companies in an emerging market environment such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 43 publications
7
27
0
Order By: Relevance
“…So, the hypothesis H4 was disapproved. This result was in accordance with the research conducted by Pepur et al (2016) who found that profitability is negatively related to leverage, so that the more profitable companies rely more on internal funds, and on this basis there is less need for financing from other sources (Pepur et al, 2016).…”
Section: Economics Of Agriculturesupporting
confidence: 91%
“…So, the hypothesis H4 was disapproved. This result was in accordance with the research conducted by Pepur et al (2016) who found that profitability is negatively related to leverage, so that the more profitable companies rely more on internal funds, and on this basis there is less need for financing from other sources (Pepur et al, 2016).…”
Section: Economics Of Agriculturesupporting
confidence: 91%
“…Our results can help policy makers adopt necessary regulatory reform to improve the CSR practices and enhance organizational legitimacy. Continued research on these lines ensures the factors that take strategic decisions in the companies the opportunity to give them a significant competitive advantage in the current competitive environment, and for the investors the attitude towards risk [103,104].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, pecking order theory suggests that profitable firms have less leverage because they generate higher cash flows and therefore prefer the use of internal funds (retained earnings) over debt or equity financing. Studies such as Chang et al (2014), Jong, Kabir, and Nguyen (2008) and Pepur, Curak, and Poposki (2016) found a negative association between profitability and leverage. With respect to information asymmetry, we expect a negative effect of profitability on leverage, as highly profitable firms will prefer internal financing over external financing.…”
Section: Profitabilitymentioning
confidence: 96%